PENGARUH MODEL PROBLEM BASED LEARNING TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK KELAS VIII SMP NEGERI 3 BATUSANGKAR - Prima Sakti, Yusti Anggun (Jurnal Edukasi dan Penelitian Matematika, 2024)
- Students must be able to solve mathematical problems, among other skills, if they are to succeed in mathematics. Grade VIII students at SMP Negeri 3 Batusangkar still have a low level of ability in this regard. Lack of student engagement is the cause. The Problem Based Learning (PBL) model was used as a solution to this problem. The purpose of this study is to determine whether the mode can improve students' abilities. It was also to determine whether the model outperformed the conventional method. Descriptive and quasi-experimental research was chosen. The Pretest-Posttest Nonequivalent Single Control Group design was used for this study. Eighth grade members of SMP Negeri 3 Batusangkar TP 2024/2025 constituted the population.  The obtained P value = 0.029 indicated the rejection of H0, so it can be said that the PBL model is superior to conventional learning, and its use leads to an improvement in the learning process.Keywords– Conventional Learning, Problem Based Learning, Problem Solving Ability